CHROMOSOMES, DNA LESION AND NUCLEAR MALFORMATION IN THE FRESHWATER TURTLE KINOSTERNON LEUCOSTOMUM (TESTUDINES: KINOSTERNIDAE) - Hernández-Guzmán, Javier (2015)
Kinosternon leucostomum is one of the common freshwater turtles in Tabasco State, Mexico. However, studies of this species are limited for this region. The pollution in aquatic ecosystems from Tabasco is increasing and the effects on wildlife have not been properly made. Therefore, a chromosomic study and DNA lesion and nuclear malformation was performed in K. leucostomum from Tabasco. The karyotype in the turtle K. leucostomum is 34 msm/A + 22 T/C(2n=56 chromosomes). Also, intracellular malformations were identified: Chromosomes and DNA damage (micronucleus), binucleated cells, trinucleated cells, tetranucleated cells, cells in apoptosis and nucleoplasmic bridge, in irregular proportions. The probable origin of cell disorders is due to the presence of contaminants in aquatic ecosystems from Tabasco.